ANALISIS PENGEMBANGAN INDUSTRI BATIK DI KOTA MADIUN (STUDI KASUS PADA BATIK PRIMADEWI MADIUN) - Windyaningrum, Theresia Liris (Widya Warta, 2017)
Madiun in Eastern Java is better known as the city of Brem and pecel; people ignore some batik companies which actually have not yet operated optimally; one of them is Batik Primadewi Madiun. From the interviews with the business owners, the greatest obstacle in batik bussiness is marketing the products. The purpose of this study was to identify anything that makes marketing the products of Batik Primadewi Madiun problematic; it was the same as finding obstacles which hindered the batik business development. Qualitative descriptive analysis and SWOT analysis showed that the factors that constrained the product marketing was the lack of marketing personnel to focus on product marketing efforts and the lack of creativity in making new batik designs. Accordingly, the formulation of strategic development of Batik Primadewi Madiun was providing marketing personnel, using internet to inspire batik designs which were more various, enriching batik designs, making the batik designers available, establishing batik trainings, ensuring batik coloring trainings, strengthening internal management, improving the utilization of worth of mouth consumers, and becoming the initiator of the establishment of batik entrepreneur forum in Madiun.